Pengaturan Perkawinan Beda Agama di Indonesia (Kajian Sejarah Sosial Hukum Islam era 1945-sekarang) - Arsal Arsal (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2013)
Heterogeneity religion professed by the people of Indonesia in its interactions will impact the marriage. Quite a lot of cases the marriage religious differences occurred in the midst of society has not been well received and is still considered problematic. On the other side of the Indonesian state already has laws about marriage, it’s just that this law does not mention any concrete related interfaith marriage. This led to multiple interpretations and does not have legal certainty in relation to interfaith marriage. Although it must be admitted that the problem of interfaith marriage has been legal vacuum, on the other hand to hold marriage it will not be dammed. In connection with this begs the question: how states organize interfaith marriage and how far the state’s recognition of marriage.